Analisis Pengaruh PP 46 Tahun 2013 terhadap Upaya Pemerintah dalam Meningkatkan Perekonomian Indonesia Melalui Sektor UMKM - MUHAMMAD SYAFIQURRAHMAN (Pusat P2M Politeknik Negeri Batam, 2017)
This study analyzes the influence of Peraturan Pemerintah Nomor 46 tahun 2013, which is the government's efforts in improving the economy of Indonesia through the Micro Small and Medium Enterprises (MSMEs). Some of the conclusion obtained from this study is that Peraturan Pemerintah Nomor 46 Tahun 2013 has positive effect on the survey of MSMEs, the implementation of Peraturan Pemerintah Nomor 46 Tahun 2013 regarding the determination of 1% of gross assist MSMEs in improving their income and capital. First, the MSMEs business operators assign profits to their business of 10-50% of gross, so 1% is not burdensome for businesses. The second conclusion is Peraturan Pemerintah Nomor 46 Tahun 2013 has positive effect on MSME tax compliance in paying taxes. Application of Peraturan Pemerintah Nomor 46 Tahun 2013 brings ease and simplification of tax calculations taxpayer, so the taxpayer MSMEs increasingly easy to calculate and pay their taxes